Comment on Cutaneous Manifestations in Obese Patients Attending Outpatient Department of a Tertiary Care Hospital - Ahmad, Bilal; Khan, Noaman; Rehman, Abdur; Ahmad, Sameed; Khan, Sadeeq (Nepal Journal of Dermatology, Venereology & Leprology, 2025)
This letter appreciates the work of Pandit et al. on cutaneous manifestations in obese patients while highlighting key methodological limitations. It recommends future studies adopt longitudinal designs, include comorbid and age-diverse populations, and apply multivariate analyses to better understand the full dermatologic burden of obesity and improve targeted screening strategies.